2020
DOI: 10.21894/jopr.2020.0093
|View full text |Cite
|
Sign up to set email alerts
|

Xylan Recovery From Dilute Nitric Acid Pretreated Oil Palm Frond Bagasse Using Fractional Factorial Design

Abstract: Pretreatment enhances bioconversion of lignocellulosic biomass by disrupting and changing the properties of its material. This work is intended to examine the influence of several variables involved in the recovery of xylan from oil palm frond bagasse (OPFB) in the pretreatment of diluted nitric acid. Through a fractional factorial design of 2 5−1 the temperature variables ranged from 37°C-90°C, time of reaction varied from 6-24 hr, solid loading ranged from 5%-20%, concentration of acid changed from 0.01%-1.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…The research on the bioconversion of lignocellulosic byproduct corn stover into the value-added fermentative product L-lactic acid using the furfural tolerant Enterococcus mundtii WX1 and Lactobacillus rhamnosus SCJ9 showed that corn stover pretreated with 1% (v/v) sulfuric acid was selected for L-LA fermentation and shows the highest efficacy of fermentable sugar with the optimal conditions achieved for the release of glucose and xylose at 24.5 g/L and 11.2 g/L, respectively, from 100 g/L pretreated corn stover at 121 • C for 30 min [102]. A similar result was presented by other researchers reported in the study of tobacco stem waste [103], palm kernel shell [104], sugarcane bagasse [105], and oil palm frond bagasse [106] that the dilute acid for chemical pretreatment is effective to attain high reactivity and generates protons that have a quick diffusion which substantially enhances the hydrolysis of amorphous cellulose chains and the solubilization of hemicellulose.…”
Section: Ethanol Synthesis Based On Lignocellulosic Materialssupporting
confidence: 85%
“…The research on the bioconversion of lignocellulosic byproduct corn stover into the value-added fermentative product L-lactic acid using the furfural tolerant Enterococcus mundtii WX1 and Lactobacillus rhamnosus SCJ9 showed that corn stover pretreated with 1% (v/v) sulfuric acid was selected for L-LA fermentation and shows the highest efficacy of fermentable sugar with the optimal conditions achieved for the release of glucose and xylose at 24.5 g/L and 11.2 g/L, respectively, from 100 g/L pretreated corn stover at 121 • C for 30 min [102]. A similar result was presented by other researchers reported in the study of tobacco stem waste [103], palm kernel shell [104], sugarcane bagasse [105], and oil palm frond bagasse [106] that the dilute acid for chemical pretreatment is effective to attain high reactivity and generates protons that have a quick diffusion which substantially enhances the hydrolysis of amorphous cellulose chains and the solubilization of hemicellulose.…”
Section: Ethanol Synthesis Based On Lignocellulosic Materialssupporting
confidence: 85%